CIVIL LAW REGULATION OF CONSULTING SERVICES (American Journal of Research in Humanities and Social Sciences, 2023)
Consulting services have become an integral part of modern business, and regulatory oversight is necessary to ensure that they operate ethically and professionally. In recent years, the consulting industry has experienced tremendous growth due to the growing demand for professional expertise and market knowledge. However, the industry has also faced numerous legal and ethical challenges, which have revealed the need for even more effective legal regulation. In this article, in order to determine more effective methods of regulation, various legal issues related to the provision of consulting services were discussed. Applying several general and private legal methods of legal research as a cognitive method, a method of analysis and synthesis, etc., the analysis of the legal conjuncture of the consulting services market was carried out. As a result of this work, results have been obtained in the form of scientific definitions, and when applied, they can be effective tools for legal regulation of consulting services.